Menyelaraskan Aspirasi Pembeli Rumah Pertama Kali Kelas Menengah dengan Persepsi Pemangku Kepentingan Studi Komprehensif di Balikpapan Utara - Maryo Inri Pratama; Hosana, Rut Nauli; Satyaninggrat, Luh Made Wisnu; Pratomo, Rahmat Aris (SPECTA Journal of Technology, 2025)
North Balikpapan District faces significant challenges in housing planning due to population growth and the announcement of the new capital city (IKN) development in East Kalimantan. Achieving optimal housing provision requires synchronization between community preferences and stakeholder perceptions. This study aims to identify the priority gaps between both parties in housing selection. The Analytical Hierarchy Process (AHP) method was used to analyze community preferences, and interviews were conducted with four key stakeholders: the government, subsidized housing developers, commercial housing developers, and the housing developer association. Secondary data were sourced from a previous study that involved a community questionnaire. The results reveal significant differences in priorities: the community prioritizes availability of facilities and infrastructure, accessibility, and environmental comfort, while stakeholders emphasize financing and house design and quality. These misalignments may affect community satisfaction regarding their living environment and access to public facilities. The implications of this study highlight the importance of policy synchronization between the government and developers to bridge this gap, ensuring more inclusive and sustainable housing development in line with the evolving needs of the community. The model derived from this study can be applied to regions experiencing rapid growth, where the majority of the population is of productive age and falls into the middle-income category, to better meet the needs of the growing population.